2016
DOI: 10.1039/c5ta06753g
|View full text |Cite
|
Sign up to set email alerts
|

Development of MgAl2O4-stabilized, Cu-doped, Fe2O3-based oxygen carriers for thermochemical water-splitting

Abstract: The commercially dominating technology for hydrogen production (i.e. steam methane reforming) emits large quantities of CO2 into the atmosphere. On the other hand, thermochemical water-splitting cycles allow to produce high purity H2 while simultaneously capturing CO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 34 publications
2
52
0
Order By: Relevance
“…During reduction, it is easy to form defective structure and cracks for the further reaction. Imtiaz et al reported that Cu metal and Fe 3 O 4 segregated from CuFe 2 O 4 spinel structure, which was in agreement with the results of Kang and Shin . When the reductive gas was CO, we speculate that such a reaction would happen: 3CuFe2O4+4CO4CO2+3Cu+2Fe3O4. …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…During reduction, it is easy to form defective structure and cracks for the further reaction. Imtiaz et al reported that Cu metal and Fe 3 O 4 segregated from CuFe 2 O 4 spinel structure, which was in agreement with the results of Kang and Shin . When the reductive gas was CO, we speculate that such a reaction would happen: 3CuFe2O4+4CO4CO2+3Cu+2Fe3O4. …”
Section: Resultssupporting
confidence: 91%
“…As discussed above, the carbon deposition was significantly suppressed by introducing potassium and copper to modify iron ore. The similar effect was also observed when iron‐based oxygen carrier was modified by copper or potassium separately . It was the first work to investigate the property of carbon deposition based on iron ore co‐decorated by potassium and copper, and the condition was different from most of the previous researches .…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations